1987
DOI: 10.1084/jem.165.5.1430
|View full text |Cite
|
Sign up to set email alerts
|

A major immunogen in Schistosoma mansoni infections is homologous to the heat-shock protein Hsp70.

Abstract: A 70,000 mol wt protein of Schistosoma mansoni was shown to be a major immunogen that invariably elicited an antibody response in infected humans. The universality of the response to this abundant antigen was confirmed in experimental animals and included the antibody response associated with the protective irradiated cercarial vaccine. We identified the 70,000 mol wt antigen as an S. mansoni homologue of the major eukaryotic heat-shock protein hsp70 by DNA sequence analysis of a cDNA insert from a lambda gt11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
43
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(48 citation statements)
references
References 17 publications
5
43
0
Order By: Relevance
“…Since the SLE autoantibodies identified in the present investigation do not recognize epitopes on the 73-kD/pI 5.5 protein deriving from conserved peptide sequences shared by other hsp70 proteins in this structurally highly homologous family (reviewed in reference 4), a comparison of nonconserved peptide sequences of the 73-kD/pl 5.5 protein with sequences of other proteins should be useful in approaching the question of molecular mimicry (epitope homology) (8,15) as a basis for microbial "triggering" of autoimmunity in SLE. For example, an immunodominant peptide of Schutosoma mansoni has amino acid sequence homology with hsp70, and may be responsible for autoantibodies to hsp70 in individuals infected with this organism (6). A related question concerns the possibility that autoantibodies to hsp70 crossreact with epitopes shared FIGURE 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Since the SLE autoantibodies identified in the present investigation do not recognize epitopes on the 73-kD/pI 5.5 protein deriving from conserved peptide sequences shared by other hsp70 proteins in this structurally highly homologous family (reviewed in reference 4), a comparison of nonconserved peptide sequences of the 73-kD/pl 5.5 protein with sequences of other proteins should be useful in approaching the question of molecular mimicry (epitope homology) (8,15) as a basis for microbial "triggering" of autoimmunity in SLE. For example, an immunodominant peptide of Schutosoma mansoni has amino acid sequence homology with hsp70, and may be responsible for autoantibodies to hsp70 in individuals infected with this organism (6). A related question concerns the possibility that autoantibodies to hsp70 crossreact with epitopes shared FIGURE 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the schistosome must adapt extensively to environments as different as fresh water and the organs of distinct hosts, the snail with internal milieu 1/3 the osmolarity of human (Di-Conzo and Basch, 1974) and temperatures ranging over 20-37 "C. Since heat-shock genes are activated in response to environmental stresses as well as during development (Bienz, 1985;Lindquist, 1986), it was of interest to study the heat-shock-protein (hsp) gene family in schistosome. The hsp70 cDNA of Schistosoma mansoni was cloned (Hedstrom et al, 1987), increased synthesis of the hsp70 protein (Yuckenberg et al, 1987) high levels of hsp70 mRNA (Blanton, 1992) were found in early schistosomula, and antibodies to schistosome hsp70 were studied in the sera of Bilharzia patients for immunodiagnosis (Hedstrom et al,1988;Moser et al, 1990). Here we report on stage specific expression of the hsp70 gene during the life cycle of S. mansoni, provide evidence that expression is controlled by a developmental program and by stress, and raise the possibility that the cercarial tail may exert a long range inhibitory effect that suppresses hsp70 gene expression in the body of the cercaria.…”
mentioning
confidence: 99%
“…Multiple autoantibodies to the self-heat shock protein, HSP90, have been described to develop in patients with systemic lupus erythematosus (SLE) (15). Therefore, it appears that an epitope homologous between microbial antigens and self-proteins such as endogenous HSP in target organs is likely to be involved in the induction of autoimmunity (2,5,8,9,16,17).…”
Section: Hiroyukimentioning
confidence: 99%